Posted by Lola on Wednesday, January 21, 2009 at 1:55pm.
Hi there, I need help with composition of functions.
I need to find fog, gof, gog, and fof and their domains for the following:
f(x) = square root of 2x +3
g(x) = x^2 + 1
if someone can help me asap that would be so great!
- Calculus - drwls, Wednesday, January 21, 2009 at 4:42pm
For g of f, substitute sqrt(2x +3) for x in g(x)
You get (2x + 3) + 1 = 2x + 4
The domain is all numbers in thnis case.
Do the others the same way. We will gladly critique your work.
- Calculus - Lola, Wednesday, January 21, 2009 at 4:58pm
okay, so i tried out subtsting x into f (x) and i got sqrt (2x^2 +5)..is that right?
and what do u mean domain is all in numbers?
can u help me with the f o f and g og?
and a side question, we got a table of values that was something like
x 1 2 3 4 5 6
f(x) 3 1 .....
so the first question is like evaulaute:
would that be
- Calculus - drwls, Wednesday, January 21, 2009 at 5:11pm
Are you trying to calculate f of g(x)?
Assuming f(x) = sqrt(2x+3) and not sqrt (2x) + 3, f of g(x) would be
sqrt [2(x^2 +1) + 3]= sqrt (2x^2 + 5)
So you would be correct.
g of g(x) = (x^2+1)^2 +1 = x^2 + 2x + 2
To your side question: yes, the first answer is 18.
Answer This Question
More Related Questions
- math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5
- math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5
- calculus - when working with composite functions, does fog=gof? how do i create ...
- Algebra - Use composition of functions to show that the functions f(x) = 5x + 7 ...
- Math - Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show ...
- Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...
- Calculus - Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their ...
- Math simplifying mixed radicals - Please help me simplify these following mixed ...
- college algebra - 1. answer the following for the given quadratic function f(x)=...
- pre calculus - 1.) If h(x)= (fog)(x) and h(x) = 3 over the square root of x+3 , ...